Pengetahuan Remaja dan Peran Teman Sebaya dengan Pencegahan Infeksi Menular Seksual - Kartini Massa; Stendy Ali (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Lack of adolescent knowledge about sexually transmitted diseases and their dangers, especially to health and the role of peers, which contributes badly to the increase in sexually transmitted diseases, especially among adolescents. This study aims to determine the relationship between adolescent knowledge and the role of peers with the prevention of sexually transmitted infections at SMA Negeri 1 Tomohon. The research design uses an analytic survey with a cross sectional approach. The sampling technique with probability sampling is simple random sampling on a sample of 92 teenagers. Data analysis used the Chi Square statistical test. The results showed that most adolescent knowledge was in the good knowledge category with a percentage of 57.6%, the role of peers was mostly in the good role category with a percentage of 63% and the prevention of sexually transmitted infections was mostly in the good prevention category with a percentage of 52.2 %. The conclusion is that there is a relationship between adolescent knowledge and the prevention of sexually transmitted infections at SMA Negeri 1 Tomohon. There is a relationship between the role of peers and the prevention of sexually transmitted infections at SMA Negeri 1 Tomohon. It is recommended to increase the role of counseling guidance through health education to add insight into knowledge so as to change the behavior of adolescents in preventing sexually transmitted infections and for adolescents to seek information about infectious diseases from various information media sources, to be active in various positive activities such as extracurricular activities held at school or other activities. other social activities and hang out with friends who have good behavior.